Unravelling hierarchical patterning of biomaterial inks with 3D microfluidic-assisted spinning: a paradigm shift in bioprinting technologies - Mohammadi, Sajad; Cidonio, Gianluca (Frontiers in Biomaterials Science, 2023)
For decades, 3D bioprinting has offered a revolutionising approach to combine living cells and biomaterials to engineer complex, yet functional constructs. However, traditional 3D bioprinting platforms fall short of the ability to pattern complex gradients of biomaterials, cells, and ultimately bio-physical properties to drive tissue formation and regeneration. Recently, 3D microfluidicassisted bioprinting (3DMB) has risen as a new hybrid approach for the fabrication of physiologically relevant tissues, adopting a microfluidic chip as functional printhead to achieve hierarchical patterning of bioinks and precise control over the microscale architecture of printed constructs, enabling the creation of multi-layered tissues. This review explores recent advancements in graded biomaterial patterning using microfluidic-assisted spinning and novel 3D bioprinting technologies. The physiological hierarchical arrangement of human tissues and the crucial role of biomaterials in achieving ordered assembly is hereby discussed. Lastly, the integration of microfluidic-assisted techniques with new bioprinting platforms is highlighted, examining the latest advancements in tissue regeneration and disease modelling.